The impact of professional development on mathematics teachers' beliefs and practices - Watson, Steven (2014)
This thesis describes the analysis of the implementation of a professional development programme for secondary mathematics teachers in England. The research used a mixed methods multiple case study design with three secondary schools. The aim of the study was to understand mathematics teachers' professional learning in the context of this professional development programme. However, through analytic generalisation, i.e. generalising to theory, these findings may have broader application to understanding teachers' professional learning. Social learning theory was used as a framework for explaining professional learning, within this are two components, observational learning and self-efficacy. Teachers learn to teach through observing behaviours and models of teaching; they implement the approaches that they are confident will be effective in their classroom - that they are self-efficacious about. I show how this explains the prevalence of traditional teacher-centred teaching in secondary mathematics and how, through observing models of alternate approaches in PD, and through developing self-efficacy in that approach, teachers can implement new approaches in their teaching. In this research, I show that the PD designed to support teachers in teaching to develop students' problem solving skills had an effect on teachers' practices: their teaching became more student-centred. It also had a positive effect on teacher self-efficacy in the suggested approach. In the qualitative analysis of multiple individual cases, I explore how observational learning processes work, in the context of the PD, and the mechanisms by which teacher self-efficacy is developed. However, a contextual analysis demonstrates that the extent to which the ideas in the PD are implemented and sustained are influenced by context at a national level and within the school. High-stakes accountability and lack of integration of PD initiatives into school strategic plans lead to PD efforts not being sustained. The main contribution of this thesis is in bringing a new theoretical approach to the field of mathematics teachers' professional development and professional learning, that of social learning theory: one that has the potential to improve the design and evaluation of professional development and teacher education in the future.